Status Quo and Enhancement Strategies for Traditional Chinese Medicine Classroom Instruction in Vocational Colleges - Hu, Zeyu (Journal of Research in Vocational Education, 2026)
Classroom instruction constitutes the central component of the educational process and serves as a critical setting for student development. Accordingly, establishing a well‑organized instructional environment and a conducive learning atmosphere is of paramount importance. This study examines the current state of Traditional Chinese Medicine (TCM) classroom teaching in vocational colleges. From the perspective of instructional reform, the study aims to enhance both the quality of classroom instruction and students’ learning motivation and initiative. Furthermore, it proposes novel pedagogical strategies and practical approaches for fostering an effective TCM classroom environment in vocational education settings. The findings are expected to serve as a reference for synthesizing experiences and improving TCM classroom teaching practices across vocational colleges and universities in China.